Action Research: Optimizing Students' 4C Skills through Gamification-Based Interactive Digital Media - Utami, Winda Sherly; Fitriana, Laila; Erdaliameta, Annisha (International Journal of Humanities, Education, and Social Sciences, 2025)
This study aims to optimize university students’ mastery of 21st-century competencies—critical thinking, communication, collaboration, and creativity (4C)—through the implementation of gamification-based interactive digital media in the learning process. Employing classroom action research with the Kemmis and McTaggart spiral model, the study was conducted in two cycles involving 27 students from the Early Childhood Education Study Program. Data were collected through structured observation to objectively monitor the implementation and outcomes of the intervention, and analyzed both descriptively and quantitatively by comparing results across cycles. The findings indicate a significant improvement in students’ 4C skills, as evidenced by an increase in average scores from 62.38 in cycle 1 to 81.77 in cycle 2, and a rise in completion rates from 26.63% to 88.89%. These results demonstrate the effectiveness of gamification-based interactive digital media in enhancing students’ 4C competencies. The study concludes that this approach not only strengthens essential 21st-century skills but also contributes to pedagogical innovation through technology integration, offering a valuable reference for the development of active learning strategies in higher education.